Investigation of mono- and polymicrobial antibiofilm activities of Defensin-like antimicrobial peptide-2 against Candida auris and Pseudomonas aeruginosa - Piketh, Aimee (University of the Witwatersrand, Johannesburg, 2024)
Multispecies infections and polymicrobial biofilms continue to increase in prevalence and clinical significance around the globe. These complex infections are challenging to treat, due to their increased expression of resistance and virulence factors, that meaningfully contribute to morbidity and mortality rates. Candida auris MRL 6057 and Pseudomonas aeruginosa ATCC 27853, have three distinct and clinically significant characteristics in common, they, i) cause nosocomial infections and outbreaks; ii) are multi-drug resistant and iii) can form biofilms. Additionally, defensin molecules have been identified as potent and broad-spectrum potential antimicrobials, in serious need of further evaluation. Therefore, the aim of this study was to determine the therapeutic efficacy of Defensin-like antimicrobial peptide-2 (DLAP-2) against the selected pathogens within mono- and polymicrobial biofilms. The broth microdilution method was used to determine the antimicrobial activity of DLAP-2. Furthermore, the effect of the compound on mono- and polymicrobial biofilms was determined at immature and mature stages of development. This was achieved using a metabolic activity assay and a microbial cell viability assay, following standard protocols. Both treated and untreated biofilms were visualised and validated using fluorescence microscopy. Additionally, the impact of DLAP-2 on membrane integrity of planktonic cell suspensions was evaluated using fluorescence microscopy. For the cytotoxicity assessment of DLAP-2, a haemolytic assay was performed. The results of this study suggest that DLAP-2 shows promising antimicrobial (with MIC and MBC/MFC values ranging from 62,5-250 μg/ml) and antibiofilm activity against polymicrobial biofilms (inhibition levels ranged from 20%-98%). The mode of antimicrobial activity for DLAP-2 was confirmed as cell membrane permeabilization. The haemolytic assay also showed that, at lower concentrations (125 μg/ml and 250 μg/ml), DLAP-2 shows low levels of toxicity (< 10%). However, at higher concentrations, a substantial increase in haemolytic activity was observed. From these results it can be concluded that DLAP- 2 shows great promise as a broad-spectrum and multispecies infection, antimicrobial agent. Further development of this anti-infective for commercial use would make DLAP-2 one of the first drugs of its kind
Master of Science in Medicine by research Department of Clinical Microbiology and Infectious Diseases School of Pathology Faculty of Health Sciences The University of the Witwatersrand, Johannesburg, South Africa 2024
Keywords: Pseudomonas aeruginosa; Biofim; Polymicrobial biofilms; UCTD; SDG-3: Good health and well-being